Prolegomena to the Study of Yeats's Plays - Saul, George Brandon (University of Pennsylvania Press, 2016)
This comprehensive study will be valuable to all Yeatsians and students of the Irish Renaissance in general, as well as anyone seriously concerned with modern drama.